Module to facilitate self-directed learning among medical undergraduates: Development and implementation - Somdatta Patra; Amir Maroof Khan; Madhu Kumari Upadhyay; Rahul Sharma; Om Prakash Rajoura; Sanjiv Kumar Bhasin (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Currently, self-directed learning (SDL) is emphasized in medical institutions all over the world. The skills of SDL enable one to be a lifelong learner, a necessity to cope up with fast-expanding medical knowledge. AIMS: This study aims to develop and implement an "SDL" module for medical undergraduates and find out their perception about the same. SETTINGS AND DESIGN: A cross-sectional study using a mixed-method design (having both qualitative and quantitative components) was conducted in the Department of Community Medicine, UCMS, Delhi, India. METHODS: A module was developed following an extensive literature review and focus group discussions with the teaching staff of the institute. First-semester undergraduate students were invited to participate in the study and asked for feedback using a semi-structured questionnaire. STATISTICAL ANALYSIS: Quantitative data were expressed in mean, range, and frequency. For qualitative data, thematic analysis was performed. RESULTS: The module was implemented with 160 students, in November for 10 hour distributed over 5 weeks. Feedback could be obtained from 130 students. Sixty-seven percent of students were satisfied and 66% reported as motivated to study the allotted topic further. Qualitative analysis showed that though the students liked the learning process based on this module, they also felt facilitators could have been more active in imparting knowledge and skills. CONCLUSIONS: To make learners equipped with the ability to learn throughout a professional learning course, SDL as a learning tool should be introduced in the medical undergraduate curriculum.